2016
DOI: 10.1002/chem.201504016
|View full text |Cite
|
Sign up to set email alerts
|

How Many Water Molecules Does it Take to Dissociate HCl?

Abstract: The potential energy surfaces of the HCl(H2O)n (n is the number of water molecules) clusters are systematically explored using density functional theory and high-level ab initio computations. On the basis of electronic energies, the number of water molecules needed for HCl dissociation is four as reported by some experimental groups. However, this number is five owing to the inclusion of entropic factors. Wiberg bond indices are calculated and analyzed, and the results provide a quadratic correlation and class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 71 publications
(90 reference statements)
4
57
1
Order By: Relevance
“…Previous studies have revealed that the thermodynamic properties and the stability order of isomers may change at different temperatures. 65,71,84 Thus, understanding the temperature dependence of cluster formation is important, especially at atmospheric temperature. However, because the wall loss of the clusters increases as the temperature decreases, it is hard to perform the relevant experiments at low temperature.…”
Section: Temperature Dependence Of Cluster Formationmentioning
confidence: 99%
“…Previous studies have revealed that the thermodynamic properties and the stability order of isomers may change at different temperatures. 65,71,84 Thus, understanding the temperature dependence of cluster formation is important, especially at atmospheric temperature. However, because the wall loss of the clusters increases as the temperature decreases, it is hard to perform the relevant experiments at low temperature.…”
Section: Temperature Dependence Of Cluster Formationmentioning
confidence: 99%
“…Aggregation simulations of SIP + H 2 O with the water molecule in random orientations and positions around the center of the SIP cluster.Table S4. Aggregation simulations of the cyclic (H 2 O) 4 cluster with an HCl molecule using three different classes of initial conditions, using different cluster-molecule distances ( d ), relative velocities ( v ), and harmonic constants ( k ), as specified.References ( 53 , 54 )…”
mentioning
confidence: 99%
“…In stark contrast to all this previous research, we focus here on the temperature sensitivity of this reaction, having in mind acid‐catalyzed processes at the typical environmental and physiological conditions of about 300 K. Indeed, there is some evidence in the literature for the stabilization of molecular HCl and recombination of salt ions in small water clusters simply by raising the temperature. However, whereas at room temperature, acid dissociation, excess protons and proton transfer have been extensively investigated in bulk water, the same cannot be said when it comes to limiting the amount of water to only a few molecules.…”
Section: Figurementioning
confidence: 99%